Design of a Reconfigurable Robotic System for Flexoextension Fitted to Hand Fingers Size - J. Felipe Aguilar-Pereyra; Eduardo Castillo-Castaneda (Applied Bionics and Biomechanics)
Due to the growing demand for assistance in rehabilitation therapies for hand movements, a robotic system is proposed to mobilize the hand fingers in flexion and extension exercises. The robotic system is composed by four, type slider-crank, mechanisms that have the ability to fit the user fingers length from the index to the little finger, through the adjustment of only one link for each mechanism. The trajectory developed by each mechanism corresponds to the natural flexoextension path of each finger. The amplitude of the rotations for metacarpophalangeal joint (MCP) and proximal interphalangeal joint (PIP) varies from 0 to 90° and the distal interphalangeal joint (DIP) varies from 0 to 60°; the joint rotations are coordinated naturally. The four R-RRT mechanisms orientation allows a 15° abduction movement for index, ring, and little fingers. The kinematic analysis of this mechanism was developed in order to assure that the displacement speed and smooth acceleration into the desired range of motion and the simulation results are presented. The reconfiguration of mechanisms covers about 95% of hand sizes of a group of Mexican adult population. Maximum trajectory tracking error is less than 3% in full range of movement and it can be compensated by the additional rotation of finger joints without injury to the user.